DRINKING WATER MICROBIOLOGICAL CONTAMINATION IN WELLS - Blohina, Tatjana; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
This article is about very important topic, about water microbiological contamination in wells in village side. Water samples were tested with Idexx metoth “Colilert - 18”test, that is ISO (International Organization for Standardization) standard 9308-2:2012 for detecting total coliforms and E.coli in water. This tests allows know answer about water microbiological contamination in 18h. The article tells about this test method and how this method works. Summary were tested five water samples. In all samples were found total coliforms, but E.coli was not found. This means that analyzed water is contaminated.